A Case of Medullary Carcinoma of the Jejunum Combined with the Intestinal Lymphangiectasia Accompanied by the Malabsorption Syndrome - O. A. Lobanova; D. S. Trusova; M. A. Afonina; V. E. Varentsoy; D. D. Protsenko; N. V. Kretova; N. B. Serezhnikova; M. A. Peshkova; N. V. Zharkov; S. E. Kochetkova; Yu. Yu. Stepanova; Z. D. Shtanev; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Aim: to present a clinical and morphological observation of an extremely rare combination of medullary carcinoma of the jejunum and intestinal lymphangiectasia in a 33-year-old patient with clinical features of malabsorption syndrome over the 10 years.Key points. An autopsy revealed a tumor formation spreading from the wall of the jejunum to the mesentery, with metastases to the mesenteric lymph nodes. The medullary carcinoma with positive expression of СD117, DOG1, EMA, PanCK, PDL-1, vimentin, mosaic non-intense expression of CA19-9, calretinin, CD10, CDX2, CEA, MUC-5AC, SATB2, and negative reaction to ALK, CD3, CD8, CD20, CD30, CD31, CD34, CD45, CD56, chromogranin, CK7, CK20, desmin. The proliferative index was high: Ki-67 > 80 %. Moreover, during the histological examination of the intestinal wall, intestinal lymphangiectasia complicated by the malabsorption syndrome was revealed.Conclusion. The uniqueness of this clinical and morphological case is in the combination of medullary carcinoma of the jejunum metastasized to the mesenteric lymph nodes with the underlying intestinal lymphangiectasia accompanied by the development of malabsorption syndrome.